Design and performance evaluation framework for seismically isolated reinforcement concrete columns subjected to blast loads. (November 2022) - Wang, Yanchao; Chen, Qingjun; Zhao, Zhipeng; Qiang, Hongfu; Yang, Kai; Wang, Xinfeng
Abstract: Isolated columns have proven to effectively improve the seismic performance of buildings, bridges, and underground structures subjected to strong earthquakes. However, considering possible explosive scenarios where unexpected blast loads occur in this vibration-isolation scenario, this study proposes a blast-based performance evaluation framework for practical columns equipped with isolators at the column top or bottom. The finite element model and simulation methods were established for isolated columns subjected to blast loads, based on which blast-induced responses could be obtained. By incorporating displacement- and capacity-based evaluation methods, the proposed evaluation framework includes static–dynamic–static coupling analysis, performance index extraction, and remaining loading capacity analysis. With the proposed framework, the blast-resistance performances of the original and isolated columns were comparatively studied by considering different explosive charges, multiple explosion heights, and various axial pressures, signifying the necessity of assessing the anti-blast performance of isolated columns. The obtained results underlined the effectiveness of the developed blast-resistance evaluation framework in quantifying the multi-performance of isolator-equipped columns, based on which the comparative performances of the original and isolated columns formed an evaluation database for reference. Benefiting from the inserted isolators at the column top (1-end) or both top and bottom (2-end), the isolated columns exhibited the same or even improved blast-resistance capacity and remaining loading capacity when subjected to multilevel blast loads. The isolated columns demonstrated a timelier reaction than the original columns. The 2-end isolators installed at column top and bottom provided the columns with lower blast-induced responses and improved stability; these are suggested, in this study, to improve high-level seismic resilience and blast resistance.